2006
DOI: 10.1007/s10750-005-1280-4
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Virioplankton in a Eutrophic Shallow Lake

Abstract: Lake Donghu is a typical eutrophic freshwater lake in which high abundance of planktonic viruses was recently revealed. In this study, seasonal variation of planktonic viruses were observed at three different trophic sites, hypertrophic, eutrophic, and mesotrophic regions, and the correlation between their abundances and other aquatic environmental components, such as bacterioplankton, chlorophyll a, burst size, pH, dissolved oxygen, and temperature, was analyzed for the period of an year. Virioplankton abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…The VPR values observed here were slightly higher than the average range described for continental environments (20-25;Maranger & Bird, 1995;Wommack & Colwell, 2000), and possibly similar to those reported in some systems with mesotrophic to eutrophic conditions, where a strong viral control has been attributed by a high rate of contact between viral particles and hosts (Bettarel et al, 2003;Weinbauer, 2004;Liu et al, 2006;Almeida et al, 2015). Thus, the trophic status or sporadic events of enrichment may promote the growth rates and/or the increase in biovolume of the host cell community, which in turn influence positively the assembly of viral particles and the burst size (Weinbauer & Höfle, 1998;Middelboe, 2000;Choi et al, 2003).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The VPR values observed here were slightly higher than the average range described for continental environments (20-25;Maranger & Bird, 1995;Wommack & Colwell, 2000), and possibly similar to those reported in some systems with mesotrophic to eutrophic conditions, where a strong viral control has been attributed by a high rate of contact between viral particles and hosts (Bettarel et al, 2003;Weinbauer, 2004;Liu et al, 2006;Almeida et al, 2015). Thus, the trophic status or sporadic events of enrichment may promote the growth rates and/or the increase in biovolume of the host cell community, which in turn influence positively the assembly of viral particles and the burst size (Weinbauer & Höfle, 1998;Middelboe, 2000;Choi et al, 2003).…”
Section: Discussionsupporting
confidence: 84%
“…The VLP values from El Neusa reservoir were within the same order of magnitude as those observed in lentic ecosystems of temperate and tropical latitudes with different trophic states, especially those with moderate to high levels of nutrients and biological productivity (Wilhelm & Smith, 2000;Bettarel et al, 2003;Liu et al, 2006;De Araújo & Godinho, 2009;Ram et al, 2011;Hardbower et al, 2012;Almeida et al, 2015). However, the variability of this study was relatively higher than in other studies, probably due to differences in temporal and spatial scales of the sampling design.…”
Section: Discussionsupporting
confidence: 69%
“…Virus densities are typically lower under ice and during the winter months (Liu et al 2006) but in some cases are equivalent to virus densities reported in warmer seasons (Filippini et al 2008;Lymer et al 2008;Wilhelm and Matteson 2008). Some studies have found that the virus to bacteria ratio can even be higher in winter than in summer (Filippini et al 2008).…”
Section: Mortality Factorsmentioning
confidence: 78%
“…While several studies have found viral abundance in freshwater lakes to be strongly correlated to chl a levels (Madan et al 2005, Liu et al 2006, Tijdens et al 2008, other studies have found viral abundance in certain lakes (Personnic et al 2009, Cheng et al 2010) and many marine systems (Maranger & Bird 1995) to be significantly correlated with bacterial abundance. These differences could indicate differences in the dominance of certain types of virioplankton (bacteriophages vs. cyanophages or algal viruses, for example) among different ecosystems.…”
Section: Abundancementioning
confidence: 96%